GAYA PENGASUHAN ORANG TUA TERHADAP PERKEMBANGAN ANAK USIA 5-6 TAHUN - Besse Arwan; Arismunandar Arismunandar; Herman Herman; Mustafa Mustafa (Kampus Akademik Publiser, 2025)
This study aims to analyze the influence of parenting style on child development. are at an important stage in the formation of social character and behavior. The parenting style applied by parents can play a significant role in shaping a child's personality, social skills, and independence. The study identified a variety of parenting styles, namely authoritative, authoritarian, permissive, and indifferent. Using quantitative methods, data was collected through questionnaires distributed to parents and observations in the classroom. The results of the study show that authoritative parenting styles have a significant positive impact on children's social and emotional development. Children who are raised in a supportive environment, but also provide clear boundaries, show better ability to interact with peers and are more confident in social situations. In contrast, authoritarian and permissive parenting styles tend to have a negative impact, with children showing difficulty in managing emotions and social relationships. These findings confirm the importance of the active role of parents in educating children at an early age. The conclusion of this study highlights the need for education for parents regarding the importance of proper parenting styles. By understanding the influences that can be caused, it is hoped that parents can develop more effective parenting patterns to support the optimal development of their children.